“Global Britain”: a course for the Asia-Pacific Region with an anti-Chinese bias - Kistanov V.O. (Восточная Азия: факты и аналитика, 2021)
The article examines the foreign policy and economic strategy of the United Kingdom in the Asian direction after the country's exit from the European Union. As part of its vision to transform the United Kingdom into a global power, London is committed to fully developing relations with the rapidly growing Asia-Pacific region. The UK intends to make up for the economic damage from the loss of markets in Europe by developing relations with the countries of the region, both bilaterally and multilaterally. The British government particularly hopes to enter the Comprehensive and Progressive Trans-Pacific Partnership (CPTPP). One of the important directions of the new strategy is the development of trade and economic relations with the ASEAN member states. The strengthening of the UK's relations with Japan allows us to talk about the creation of a quasi-alliance between Tokyo and London. However, the UK's economic and security aspirations in the Asia-Pacific region are often motivated by the need to contain the increasing ambitions of China.